Biofiltration of styrene using composite beads of compost as modified biofilter media - Singh S.; Rai B.N.; Singh R.S. (My University, 2025)
Compost is one of the widely used and most efficient biofilter media reported in the literature with only few limitations such as problem of compaction during long term operation and requirement of some macro and micro nutrients during its operation. In the present study, compost based modified biofilter media was prepared with objective to remove above limitations and tested against styrene loaded air stream in a biofilter inoculated with mixed culture of microorganism for a period of 123 days without supply of nutrients. Characterisation results of the media showed that it has most of the favourable properties required for bio filtration. The maximum removal efficiency of 98.2% was obtained at the styrene loading of 520.2g m-3 h-1. The maximum elimination capacity of 870.8 g m-3 h-1was obtained at the styrene loading of 980.9 g m-3 h1. Michaelis-Menten kinetic constants ECmax and Ks were also estimated and found to be 1139.24 gm-3hr-1 and 1.77 g m-3 for styrene. The ECmax calculated by kinetic model is more than maximum elimination capacity obtained in the experiment which indicates that there is still scope for improving the performance of biofilter by optimizing the process parameter.